Shareholder Wealth Consequences of Insider Pledging of Company Stock as Collateral for Personal Loans - Dou, Ying; Masulis, Ronald W.; Zein, Jason (Review of Financial Studies, 2019)
[We study a widespread yet under-explored corporate governance phenomenon: the pledging of company stock by insiders as collateral for personal bank loans. Utilizing a regulatory change that exogenously decreases pledging, we document a negative causal impact of pledging on shareholder wealth. We study two channels that could explain this effect. First, we find that margin calls triggered by severe price falls exacerbate the crash risk of pledging firms. Second, since margin calls may cause insiders to suffer personal liquidity shocks or to forgo private benefits of control, we hypothesize and find that pledging is associated with reduced firm risk-taking.]